THE INFLUENCE OF ENGLISH SUBTITLED CARTOON VIDEOS IN TEACHING LIS-TENING ABILITY (A-QUASI EXPERIMENTAL AT EIGHT GRADE OF SMPN 05 BENGKULU IN ACADEMIC YEAR 2021/2022) - Agustin, Zetry; Akbarjono, Ali; utami, valisneria (Yayasan Darussalam Bengkulu, 2022)
The purposes of this research was to find out whether there is significant difference of students’ listening ability taught by using English subtitled cartoon videos and without taught at SMP 5 Bengkulu. The design of this research was an experimental research, which used quasi-experimental research. The subject of the research was the eight grade students SMP 5 Bengkulu. The researcher used cluster random sampling as a sampling technique and took two classes as the sample. Class VIII A as the experimental class which consist of 30 students and VIII B as the control class which consist of 30 students. The instrument of this research is a test. The data of research were collected by two kinds of test, pre-test and post-test. Pre-test was used to determine the students’ listening ability before getting the treatment and post-test was used to determine the students’ listening ability after getting treatment. In analyzing the data, researcher adopted independent and paired sample T-test formula by using SPSS version 16. Based on the analysis of t-test formula, the sig. value is 0.000. It could be stated that 0.000<0.05. It means that null hypothesis (Ho) is rejected, while alternative hypothesis (H1) is accepted. The writer concluded that there is significant effect of using English subtitled cartoon videos to students’ listening ability at SMP 5 Bengkulu.